2023
DOI: 10.1177/09697330231164762
|View full text |Cite
|
Sign up to set email alerts
|

Examining moral injury in clinical practice: A narrative literature review

Abstract: Healthcare workers experience moral injury (MI), a violation of their moral code due to circumstances beyond their control. MI threatens the healthcare workforce in all settings and leads to medical errors, depression/anxiety, and personal and occupational dysfunction, significantly affecting job satisfaction and retention. This article aims to differentiate concepts and define causes surrounding MI in healthcare. A narrative literature review was performed using SCOPUS, CINAHL, and PubMed for peer-reviewed jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The inability to provide nursing care that is congruent with one’s education and professional values could increase nurses’ cognitive dissonance and consequently lead to moral distress. 61 Constraints within the health care system 61 , 62 may be forcing nurses to make decisions which go against their values, thus increasing the risk of moral distress, which is known to increase burnout symptoms 21 , 62 and turnover intentions. 21 While there are many studies regarding the moral injuries that occurred among nurses during the pandemic, 17 , 21 , 44 , 62 there needs to be additional research examining the complex relationship between work environment, scope of practice, moral distress, and turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…The inability to provide nursing care that is congruent with one’s education and professional values could increase nurses’ cognitive dissonance and consequently lead to moral distress. 61 Constraints within the health care system 61 , 62 may be forcing nurses to make decisions which go against their values, thus increasing the risk of moral distress, which is known to increase burnout symptoms 21 , 62 and turnover intentions. 21 While there are many studies regarding the moral injuries that occurred among nurses during the pandemic, 17 , 21 , 44 , 62 there needs to be additional research examining the complex relationship between work environment, scope of practice, moral distress, and turnover intentions.…”
Section: Discussionmentioning
confidence: 99%
“…For the pharmacist, these internal and external tensions contribute to the cognitive dissonance that underpins moral distress. 8 Moral Injury in Health Care The topic of moral distress experienced by health care practitioners, including pharmacists, has recently received increased attention. 9,10 Isolated incidents of moral distress, in and of themselves, can be overcome in passing, especially in individuals with moral resilience.…”
Section: Commentarymentioning
confidence: 99%
“…15 Moral distress and burnout experienced by stewardship pharmacists can also be aroused by stressors other than daily clinical activities, such as presented in this case; additional administrative duties (eg, formulary review, drug shortage management) might result in additional moral distress for pharmacists charged with allocating costly and scarce resources for an entire institution or community. 1,8 Several potential mediating factors have been described in the literature that make individuals more vulnerable to moral injury, including constraints specific to a task or institution, as well as social determinants of health. 8,16 Factors that place ID pharmacists at heightened risk of moral injury include the following: (a) their inherent position in the decisional hierarchy of medical practice; (b) their complex role in balancing direct clinical and administrative responsibilities; (c) others' negative perception of their role as stewards, leading to their being dismissed and labeled with the pejorative terms gatekeeper and antibiotic police; and (d) their insufficient awareness of and training in bioethical principles during pharmacy education.…”
Section: Commentarymentioning
confidence: 99%
“…For example, Zhao and colleagues found that workplace violence had a significant negative impact on nurses' thriving 15. Additionally, healthcare systems with excessive administrative burden, a lack of autonomy, inadequate support and resources, and poor communication promote moral distress and moral injury in nurses, the antithesis of thriving 16…”
Section: Conceptual Model Of Thriving In Nursingmentioning
confidence: 99%